2021
DOI: 10.7759/cureus.15991
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiophobia Post Total Hip Arthroplasty: A Retrospective Study

Abstract: IntroductionOne of the major psychological factors that can affect the outcome of hip arthroplasty is postoperative kinesiophobia, which is defined as a fear of movement. The effect of kinesiophobia and excruciating pain has not been widely explored in hip arthroplasty literature especially in Saudi Arabia. AimThis study aimed to investigate kinesiophobia and pain catastrophizing after total hip arthroplasty (THA) in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In our study, the pain level reported by the participants was probably too low to influence functional abilities, 32 and this might have influenced the self-perceived health status in turn, leading to fear of movement decrease in the first days after surgery. 31 In addition, the use of painkillers might have hindered between-group differences related to the preoperative intervention. Finally, previous studies indicated that Action Observation and Motor Imagery benefits on pain and fear of movement would be more visible at longer follow-up in patients suffering from chronic musculoskeletal conditions, when compared to subjects with acute postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the pain level reported by the participants was probably too low to influence functional abilities, 32 and this might have influenced the self-perceived health status in turn, leading to fear of movement decrease in the first days after surgery. 31 In addition, the use of painkillers might have hindered between-group differences related to the preoperative intervention. Finally, previous studies indicated that Action Observation and Motor Imagery benefits on pain and fear of movement would be more visible at longer follow-up in patients suffering from chronic musculoskeletal conditions, when compared to subjects with acute postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pain represents one of the most affecting factors on functional recovery after total hip arthroplasty, which is also positively correlated with fear of movement. 31 While advantages for patients receiving Action Observation and Motor Imagery were expected, several factors might concur in explaining the lack of effects. In our study, the pain level reported by the participants was probably too low to influence functional abilities, 32 and this might have influenced the self-perceived health status in turn, leading to fear of movement decrease in the first days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical nurses work with patients with kinesiophobia and that occurs more frequently among patients with orthopaedic disorders, such as low back pain and total hip replacements. Felício et al (2021) found that the incidence of kinesiophobia in patients with low back pain was 57.3%, and Alsaleem et al (2021) found that the incidence of kinesiophobia in patients with total hip replacement was as high as 62.2%. Fear is an important psychosocial factor that affects the pain experience of people, and kinesiophobia leads to changes in behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The role that kinesiophobia plays in chronic shoulder pain intensity and disability has been explored [ 7 ]. There was a high prevalence of kinesiophobia among patients who underwent total hip arthroplasty, shoulder arthroscopy, spinal surgery, and anterior cruciate ligament reconstruction [ 6 , 8 10 ]. Pain intensity is directly correlated with the presence of kinesiophobia.…”
Section: Introductionmentioning
confidence: 99%